ANALISIS PERBEDAAN KINERJA KEUANGAN PERUSAHAAN ANTARA SEBELUM DAN SESUDAH BERPARTISIPASI DALAM INDONESIA SUSTAINABILITY REPORTING AWARDS (ISRA) SELAMA PERIODE 2007-2011 - YUNISTIA FIRMANI, SHEILA Yunistia (Jurnal Akuntansi AKUNESA, 2013)
The aim of the study is to determine the differences between company's financialperformance before and after participating within ISRA during the period 2007-2011by using approach quantitative descriptive. The data used by researchers is financialperformance with profitability ratio as ROA and ROE. Data obtained from thecompanies listed in Indonesia Stock Exchange and the companies that participated inISRA continuous period of 2007-2011. The result of the study show that there aredifferences in financial performance (using ROA and ROE as proksi of financialperformance) between before and after participating within ISRA during the period2007-2011.Keywords : Indonesia Sustainability Reporting Awards (ISRA), Return On Asset,Return On Equity